Diet and sexual segregation of desert bighorn sheep (Ovis canadensis mexicana Merriam) in Sonora, Mexico (Agro Productividad, 2021)
Objective: To determine the diet of the desert bighorn sheep and to identify differencesin its composition between sexes during the reproductive and sexual segregation periods.Design/methodology/approach: The study was carried in the UMA Rancho NocheBuena, Hermosillo, Sonora. The microhistological technique and a cell catalog of plantsfrom the study area were used to identify plant species present in fecal samples ofbighorn sheep. The relative frequency, the Shannon-Weaver diversity index and theKulczynski similarity index were determined by sex and period (reproductive andsegregation)Results: The diet of bighorn sheep included 40 species, being herbaceous (36.1 ±4.4%) and grasses (26.8 ±8.9 %) the most common. The diet of males during thesegregation period was mainly composed of grasses (36.2%) and female diet byherbaceous (30%) and grasses (29.8%). No differences were found in the diversity ofthe diet of males and females in the segregation period (H '= 1.0) and in general, their diets were very similar (80%).Limitations/implications: To collect a greater number of fecal samples by sex andperiod (reproductive and segregation) and to analyze the nutritional content of plantsconsumed by bighorn sheep.Findings/conclusions: In this study, the sexual segregation exhibited by the bighornsheep in the Wildlife Management and Conservation Unit Rancho Noche Buena was notdue to food preferences.